Single Amino Acid Changes in the Ryanodine Receptor in the Human Population Have Effects In Vivo on Caenorhabditis elegans Neuro-Muscular Function - Graham, Brittany; Shaw, Marie-Anne; Hope, Ian A. (Frontiers in Genetics, 2020)
The ryanodine receptor mediates intracellular calcium ion release with excitation of nerve and muscle cells. Ryanodine receptor missense variants cause a number of myopathologies, such as malignant hyperthermia, and have been linked with various neuropathologies, including Alzheimer’s disease. We characterized the consequences of ryanodine receptor variants in vivo. Eight Caenorhabditis elegans strains, with ryanodine receptor modifications equivalent to human myopathic RYR1 variants, were generated by genome editing. In humans, these variants are rare and confer sensitivity to the inhalational anaesthetic halothane when heterozygous. Increased sensitivity to halothane was found in both homozygous and heterozygous C. elegans. Close analysis revealed distinct subtle locomotion defects, due to the different single amino acid residue changes, even in the absence of the external triggering agent. Distinct pre- and postsynaptic consequences of the variants were characterized through the responses to cholinergic pharmacological agents. The range of phenotypes reflects the complexity of the regulatory inputs to the ryanodine receptor and the criticality of the calcium ion channel opening properties, in different cell types and with age. Ryanodine receptors with these single amino acid residue changes still function as calcium ion channels, but with altered properties which are likely to have subtle consequences for human carriers of such variants. The long-term consequences of subtly altered calcium ion signalling could be cumulative and may be focussed in the smaller nerve cells rather than the more robust muscle cells. It was important to assess phenotypes in vivo to properly appreciate consequences for a whole organism.